The Critical Aspect on Fair Value Accounting And Its Implication To Islamic Financial Institutions. - Majid, Jamaluddin; Haliding, Safri (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2014)
The Critical Aspect on Fair Value Accounting And Its Implication To Islamic Financial Institutions. Fair value accounting (FVA) paradigm replaced the historical cost accounting (HCA) in the development of accounting standards that FVA is more relevant that HCA probably did not provide the real financial and income information. This paper tries to explore critical aspects of the fair value accounting and its implications to Islamic Financial Institutions implications. This study concludes that that fair value accounting measurement provides many critical aspects to be implemented to Islamic Financial Institutions (IFIs). AAOIFI proposed cash equivalent value as respond to fair value measurement that cash equivalent value when the attribute condition are present such as the relevance, reliability and understandability of the resulting information DOI:10.15408/aiq.v6i2.1236